Sign up ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have $f_k(x)=kx-\lfloor kx \rfloor$, where $k\in \mathbb N$ and $x\in\{0,1\}$ and $x\in \mathbb Q$. When I plug in some numbers it seems obvious that $$ f_k(x)+f_k(1-x)=1 $$ for example $k=28, x=\frac{21}{38}$ gives $$ 28\frac{21}{38} - \lfloor 28\frac{21}{38} \rfloor + 28\frac{17}{38} - \lfloor 28\frac{17}{38} \rfloor = \frac{294}{19} - 15 + \frac{238}{19} - 12 = \frac{532}{19} -27=1 $$ but I have trouble to prove this in general. I get $$ (x+(1-x))k-\lfloor kx\rfloor - \lfloor k(1-x)\rfloor=k -\lfloor kx\rfloor- \lfloor k(1-x)\rfloor $$ How to continue?

share|cite|improve this question
Oh sorry there's an error $\lfloor kx \rfloor \neq (k-1)$...But the problem remains... – draks ... Apr 18 '14 at 20:33
You should get $\lceil kx\rceil - \lfloor kx\rfloor$, by the way. – Daniel Fischer Apr 18 '14 at 20:33
Separate the problem into two cases, $kx \in Z$ and $kx \not \in \mathbb Z$ . For the second case, represent $kx$ as $a + b$ for $a \in \mathbb Z$ and $0 < b < 1$. – DanielV Apr 18 '14 at 20:39

2 Answers 2

up vote 2 down vote accepted

Continuing your calculation: \begin{align}k-\lfloor kx\rfloor-\lfloor k-kx\rfloor=k-\lfloor kx\rfloor-k-\lfloor-kx\rfloor=-\lfloor-kx\rfloor-\lfloor kx\rfloor=\lceil kx\rceil-\lfloor kx\rfloor\end{align} So it's $0$ if $kx\in\mathbb Z$, else it's $1$.

share|cite|improve this answer

$f_k(x) = \{kx\}$. Then let $f_k(x) = a$. Note that $f_k(1-x) = \{k(1-x)\} = \{-kx\} = \{1-kx\}$ since $\{k\} = 0$ so the result follows.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.